(untitled) (Proceedings of the International Conference on Public Health, 2026)
Occupational injuries remain a major safety and health concern in Thailand. In 2023, over 80,000 cases were reported, with Songkhla province having the highest proportion of severe cases (4.42%) in the southern region. Although laws and preventive measures are in place, occupational injuries still occur frequently. This study aimed to assess the prevalence and factors associated with severe occupational injuries among employees in Songkhla. This retrospective study used secondary data from the Occupational Safety and Health Center Region 9, Ministry of Labour. The sample included 1,920 employees from 769 companies in 2023, collected using a standardized form. Descriptive statistics summarized the characteristics of injury cases. Logistic regression was used to identify factors associated with severe injuries, using adjusted odds ratios (AOR) and 95%CI. Model precision was evaluated with the Hosmer–Lemeshow test and ROC curve. Among 1,920 employees, 1,020 (53.1%) sustained severe injuries. Most occurred in February (AOR=1.8; CI 1.1–2.9), March (AOR=1.9; CI 1.2–3.0), and November (AOR=2.1; CI 1.3–3.4). Higher odds were found in agriculture/fishery sectors (AOR=3.2; CI 1.0–10.1), deep lacerations (AOR=2.2; CI 1.7–2.8), and fractures/dislocations (AOR=3.9; CI 2.9–5.1). Lower odds were found for injuries to the head/face/neck (AOR=0.1; CI 0.01–0.6) and hip/waist/torso (AOR=0.1; CI 0.01–0.9). Leading causes included falling objects (AOR=1.5; CI 1.0–2.3), falls from height (AOR=1.7; CI 1.0–3.1), and transport-related accidents (AOR=4.0; CI 1.8– 9.0). Workplaces with ≥500 employees had higher odds (AOR=1.5; CI 1.0–2.1). The model showed good fit (χ2=5.59, p=0.232) and fair discrimination (AUC=0.705). Severe injuries were significantly associated with month, industry type, nature and location of injury, accident cause, and company size. These findings underscore the need for targeted interventions in high-risk sectors, Strengthened enforcement at key times, and sector- specific prevention programs.